EFEKTIVITAS PENGOLESAN DAN PIJAT PERINEUM DENGAN MENGGUNAKAN MINYAK ZAITUN TERHADAP KEJADIAN RUPTURE PERINEUM - Nina Fitri; Visti Delvina; Feibrina Handayani (Universitas Fort de Kock Bukittinggi, 2023)
Perineal rupture is one of the causes of postpartum hemorrhage. This rupture is the second cause of bleeding where the most maternal deaths are bleeding (1,280 cases), and it occurs in almost every first delivery and not infrequently also in subsequent deliveries. This study aimed to determine The Effectiveness of Perineal Lubrication and Massage by Using Olive Oil toward Rupture During Labor at BPM Mawar Kerinci in 2021. The type of this study was group comparison pre-experimental design. Statistical test with Whitney Mann test. The population was primigravida pregnant women with a minimum gestational at 36 weeks. There were 30 pregnant women that chosen as the samples. It was divided into 2 groups, namely a group of pregnant women with olive oil and a group of pregnant women with perineal massage with olive oil. The results showed that in the olive oil smear group, there were 5 people (33.33%) and first-degree rupture were 6 people (40.0%), and as many as 4 people (25.67%) did not experience rupture of the perineum. In the perineal massage group with olive oil, 8 people (53.33%) did not have perineal rupture and 7 people (46.67%) experienced grade 1. Based on the analysis of the Whitney Mann test found a significant p value of 0.033 (< 0.05), it means that there was a significant difference between perineal rubbing and massage with olive oil on the incidence of perineal rupture. In short, it can concluded and perineal massage with olive oil can prevent perineal rupture better than applying olive oil in normal delivery. This program can be applied in midwifery clinical practice, especially for primigravida pregnant women.Keywords: Perineal rupture, perineal massage, olive oil